Adobe Dreamweaver CS6 digital classroom - Osborn, Jeremy (Digital classroom (Indianapolis, Ind.), 2012)
Learn Dreamweaver CS6 at your own speed with this complete training package Dreamweaver is the industry standard software for professional website design, with more than 90 percent of the market. In this book-and-DVD package, expert instructors provide a complete course in basic Dreamweaver that you can access at your own speed.